2002
DOI: 10.1590/s0001-37652002000100006
|View full text |Cite
|
Sign up to set email alerts
|

The lizard cerebral cortex as a model to study neuronal regeneration

Abstract: The medial cerebral cortex of lizards, an area homologous to the hippocampal fascia dentata, shows delayed postnatal neurogenesis, i.e., cells in the medial cortex ependyma proliferate and give rise to immature neurons, which migrate to the cell layer. There, recruited neurons differentiate and give rise to zinc containing axons directed to the rest of cortical areas, thus resulting in a continuous growth of the medial cortex and its zincenriched axonal projection. This happens along the lizard life span, even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 74 publications
1
32
2
Order By: Relevance
“…In this study, we report and characterize distributions of NADPHd+ and DCX+ neurons in the adult T. hispidus hippocampal formation, which is a structure with notably high neurogenic activity that is putatively homologous to the mammalian hippocampus [Font et al, 2002;López-García et al, 2002;Marchioro et al, 2005]. We found that the DMC (also called large-celled MC), especially the IPL, has a high density of NADPHd+ neurons, while the MC (also called small-celled MC) has a considerably lower density and a complete absence of NADPHd+ neurons in the CL.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we report and characterize distributions of NADPHd+ and DCX+ neurons in the adult T. hispidus hippocampal formation, which is a structure with notably high neurogenic activity that is putatively homologous to the mammalian hippocampus [Font et al, 2002;López-García et al, 2002;Marchioro et al, 2005]. We found that the DMC (also called large-celled MC), especially the IPL, has a high density of NADPHd+ neurons, while the MC (also called small-celled MC) has a considerably lower density and a complete absence of NADPHd+ neurons in the CL.…”
Section: Discussionmentioning
confidence: 99%
“…A number of classical papers have described the structure and connections of the telencephalon of lizards from various squamate families, including actively foraging species, such as Tupinambis nigropunctatus (Lohman and Van WoerdenVerkley 1978) and T. teguxin (Teiidae; Lohman and Mentink 1972) and Podarcis hispanica (Lacertidae; Olucha et al 1988;Lopez-Garcia et al 2002), or sedentary species, such as Iguana iguana (Iguanidae ;Northcutt 1967;Bruce and Butler 1984) and Gekko gecko (Gekkonidae; Bruce and Butler 1984;Hoogland and Vermeulen-Vanderzee 1989). Anatomic forebrain atlases have been published for Anolis carolinensis (Greenberg 1982) and G. gecko (Smeets et al 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Lesioning of the MC and DC of turtles produces deficits in spatial memory and the ability to navigate a maze [Rodriguez et al, 2002;López et al, 2003]. In squamate reptiles, lesioning of the MC causes similar disruption of the ability to navigate [Lopez-Garcia et al, 2002;Day et al, 2001]. Day et al [1999a, b; suggested that relative size differences in both the MC and DC of two lizards of the genus Acanthodactylus with contrasting spatial demands may not be related to differences in the lizards' ability to carry out bird-or mammallike spatial navigation, because no such differences were detected in laboratory tests aimed at quantifying such abilities.…”
mentioning
confidence: 99%